HaNDL Syndrome Presenting with Thunderclap Headache. (31st May 2021) - Parasram, Melvin; Malhotra, Ashwin; Yoo, Andrea S.; Mir, Saad A.
Abstract : Introduction . Transient headache and neurologic deficits with cerebrospinal fluid lymphocytosis (HaNDL) is defined as a secondary, nonvascular headache disorder characterized by the findings described in its name. Patients with HaNDL syndrome typically present with gradual onset migrainous headaches of moderate to severe intensity with transient neurological symptoms. Case Report . We discuss a patient who presented with thunderclap headache, recent transient neurologic deficits, and was ultimately diagnosed with HaNDL after an extensive neurologic evaluation. Conclusion . Thunderclap headache has very rarely been described in patients with HaNDL. After excluding emergent and secondary causes, HaNDL should be considered in patients with thunderclap-quality headaches, particularly when there is a history of transient neurological symptoms.